(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
In this article, we analyze the implementation of smart city systems in Uzbekistan. The trends and perspectives of integrating information and communication technologies (ICT) into urban environments in Uzbekistan are examined. The criteria of trust, transparency, and accountability, specific to corporate governance, are gaining importance in improving the investment environment, ensuring financial stability, and promoting sustainable economic growth